The Snakes and Ladders Game: Developing the Early Childhoods’ Cognitive Ability at Cendrawasih II Kindergarten - Kuncoro, Agus (Journal Corner of Education, Linguistics, and Literature, 2024)
A game is a tool functions to develop various aspects of early childhoods’ development. One of games is the snakes and ladders which can develop the early childhoods’ cognitive ability. This study aims to determine the development on the early childhoods’ aged 5-6 years cognitive ability through the use of the snakes and ladders game. This study employs qualitative research method under descriptive approach. The findings of this study show that the snakes and ladders game is beneficial to develop the early childhoods’ cognitive ability. The evidence is proved by the early childhoods’ response that through playing the snakes and ladders game they are able to recognize the symbols of numbers, know and memorize numbers from 1 to 56 that is written in the board of snakes and ladders game, recognize various types of colors, shapes, and understand the characteristics of the animals contained in the snakes and ladders game. In conclusion, the snakes and ladders game can be an effective game to develop the early childhoods’ cognitive ability, besides that the game makes them feel happy to play.